Rhythmic changes in Fabry disease: Inversion and non-oscillatory pattern in 6-sulfatoxymelatonin daily profile - Vallim, Julia Ribeiro da Silva; Amaral, Fernanda Gaspar do; Cipolla-Neto, José; D’Almeida, Vânia (Chronobiology international, 2019)
Fabry disease is a progressive disease characterized by an enzymatic deficiency of acid alpha-galactosidase and glycosphingolipids storage within the lysosomes. The disease has two phenotypes: classic and nonclassic. Excessive daytime sleepiness is a common sign reported by patients and can be caused by a circadian rhythm sleep disorder. Activity and rest cycle, variation of body temperature and melatonin biosynthesis are known rhythmicity markers. In the face of these evidences, our goal was to evaluate the rhythmic profile in Fabry's disease patients using rhythmicity markers. For this purpose, we recruited 17 patients diagnosed with Fabry disease (11 classic and 6 nonclassic variant) that answered the Epworth Sleepiness Scale and the Morningness-Eveningness questionnaire adapted from Horne and Ostberg; recorded activity and body temperature rhythms by an actigraphy during at least 10 days and collected urine to assess 6-sulfatoxymelatonin excretion load during the day (from the second urine in the morning until 7 p.m.) and night (starting from 7 p.m. until the first urine in the morning of the following day). We observed that control subjects presented higher excretion load of 6-sulfatoxymelatonin during the night (p < 0.05, d = 7.8), as expected. Patients with the nonclassic variant presented an inversion on 6-sulfatoxymelatonin daily profile (p < 0.05, d = 3.8) and there was no difference between the day and night profile of classic variant patients when compared to the other two groups. Patients with the classic variant also presented temperature period greater than 24 hours (p < 0.05, d = 2.0). Therefore, we came to the conclusion that there is an alteration in the circadian rhythms in Fabry disease patients, evidenced by modifications in the 6-sulfatoxymelatonin daily profile and in the body temperature rhythm period.